PMO-045 Perioperative dietetic consultation leads to improved nutritional status at 2 week follow-up in patients with oesphagogastric cancer. (28th May 2012) - Bakewell, L; Noble, F; Lam, V; Walters, E; Underwood, T
Abstract : Introduction: Patients with oesophagogastric cancer are at high risk of malnutrition. 1 The aim of this study was to assess the effect of advice provided by a dietitian peri-operatively on nutritional status at first surgical follow-up. The period studied was prior to specialist dietetic services being funded, resulting in lack of capacity to see all patients referred. Methods: Consecutive records (n=60) of patients who underwent oesophagogastric resection between August 2010 and November 2011 and referred to the dietetic service were reviewed. Jejunally (n=19) and parenterally fed (n=4), palliative (n=3), stromal tumour resection (n=1), peri-operative deaths (n=1) and incomplete records (n=1) were excluded. Anthropometrics were collected on admission and at first surgical outpatient follow-up. Number of consultations and time spent with a dietitian was recorded. Data for patients referred but not seen was compared to those who received dietetic input. Effect was measured as percentage weight loss. Tests for normality were performed. T-test was used to determine significance. Results: 31 patients were included in the study. All were initiated on oral nutrition post-operatively. n=21 received dietetic input and n=10 did not. Patient characteristics were similar between both groups apart from tumour differentiation (p=0.046), sex (p=0.023) and weight loss on admission (p=0.148). Mean length of stay=12.8 days (SE 1.1) and time to follow-up= 22.8 days (SE 2.2) (p=ns). Weight loss percentage at follow-up between patients seen and not seen by a dietitian was 7.87 (SE 0.70) and 11.66 (SE 1.24) respectively (p=0.008). Adjusting for sex, tumour differentiation and weight loss on admission did not effect the result (6.88 (SE 0.93), 11.49 (SE 1.07) p=0.005). In the intervention group mean reviews by a dietitian=2.4 (SE 0.3) and time spent=138 min (SE 14). Regression analysis showed a tendency for attenuation of percentage weight loss on increasing time with a dietitian (r=0.33; p=0.142). Conclusion: Dietetic advice peri-operatively significantly attenuates weight loss at first outpatient follow-up. This effect may improve with increasing time spent with a dietitian. The data supports the Improving Outcomes Guidance on access to dietetic expertise. Although not found in this study, malnutrition is known to increase readmission and hospital stay. 2 Competing interests: None declared. References: 1. Bozzetti F. Screening the nutritional status in oncology: a preliminary report on 1000 outpatients. Support Care Cancer 2009;17 :279–84. 2. Correia MI, Waitberg DL. The impact of malnutruition on morbidity, mortality, length of stay and costs evaluated through a multivariate model analysis. Clin Nutr 2003;22 :235–9.